Establishing a Causal Link between Ankylosing Spondylitis and Inflammatory Bowel Disease: A Review of the Literature - Jaclyn Rivington; Michael Gillett (University Library System, University of Pittsburgh, 2016)
The link between ankylosing spondylitis and inflammatory bowel disease is unclear, however it is hypothesized that there is a causal link between the inheritance of a human leukocyte antigen B27 allele and the development of inflammatory bowel disease symptoms in ankylosing spondylitis patients. Research articles assessing the relationship between ankylosing spondylitis, inflammatory bowel disease and the human leukocyte antigen B27 antigen were collected from the PubMed database. Patients expressing the human leukocyte antigen B27 allele have a demonstrated predisposition to developing symptoms of inflammatory bowel disease and sacroiliitis in ankylosing spondylitis. However, human leukocyte antigen B27 is considered to be just a contributing factor in the disease, as interleukin-23, natural killer cells, and alterations to the microbiome have also demonstrated an active role in the development of symptoms. More longitudinal studies using larger cohorts are needed to further substantiate a direct causal relationship between ankylosing spondylitis and inflammatory bowel disease.